Clays and Clay Minerals, Vol. 58, No. 4, 542–557, 2010. - Bishop, Michael E.; Jaisi, Deb P.; Dong, Hailiang; Kukkadapu, Ravi K.; Ji, Junfeng (The Clay Minerals Society, 2010)
Fe-reducing micro-organisms can change the oxidation state of structural Fe in clay minerals. The interactions with complex clays and clay minerals in natural materials remain poorly understood, however. The objective of this study was to determine if Fe(III) in loess was available as an electron acceptor and to study subsequent mineralogical changes. The loess samples were collected from St. Louis (Peoria), Missouri, USA, and Huanxia (HX) and Yanchang (YCH), in the Shanxi Province of China. The total Fe concentrations for the three samples was 1.69, 2.76, and 3.29 wt.%, respectively, and Fe(III) content was 0.48, 0.69, and 1.27 wt.%, respectively. All unreduced loess sediments contained Fe (oxyhydr)oxides and phyllosilicates. Bioreduction experiments were performed using Shewanella putrefaciens CN32 with lactate as the sole electron donor and Fe(III) in loess as the sole electron acceptor with and without anthraquinone-2, 6-disulfonate (AQDS) as an electron shuttle. Experiments were performed in non-growth (bicarbonate buffer) and growth (M1) media. The unreduced and bioreduced solids were analyzed by X-ray diffraction, Mo¨ssbauer spectroscopy, diffuse reflectance spectroscopy, and scanning electron microscopy/energy dispersive spectroscopy. Despite many similarities among the three loess samples, the extent and rate of Fe(III) reduction varied significantly. In the presence of AQDS the extent of reduction in the non-growth experiment was 25% of total Fe(III) in HX, 34% in Peoria, and 38% in YCH. The extent of reduction in the growth experiment was 72% in HX, 94% in Peoria, and 65% in YCH. The extent of bioreduction was less in the absence of AQDS. Overall, AQDS and the M1 growth medium significantly enhanced the rate and extent of bioreduction. Fe(III) in (oxyhydr)oxides and phyllosilicates was bioreduced. Siderite was absent in control samples, but was identified in bioreduced samples. The present research suggests that Fe(III) in loess sediments is an important potential source of electron acceptors that could support microbial activity under favorable conditions.
Bioavailability Of Fe(iii) In Loess Sediments: An Important Source Of Electron Acceptors
gsccm58409-bis.pdf -- 628KB
Keywords: Periodicals; Geology; Bioreduction; Iron; Loess; Mineral Transformation; Shewanella putrefaciens